Rush hour - Ratner, Brett; Cheng, Long, 1954-; Tucker, Chris; Wilkinson, Tom, 1948-2023 (Burbank, Calif. : New Line Home Video, 2007)
A tough Hong Kong cop and a fast-talking LAPD detective join forces to solve the kidnapping of a Chinese diplomat's daughter, despite the fact that they can't stand each other.
Originally released as a motion picture in 1998.
Features: audio commentary by Brett Ratner; isolated score with commentary by Lalo Schifrin; deleted scenes; featurette: "A piece of the action: behind the scenes of Rush hour"; cast & crew biographies; original theatrical trailer; short film: "Whatever happened to Mason Reese?,"; music videos: "How deep is your love" (featuring Dru Hill), "Nuttin' but love" (featuring Heavy D).
Jackie Chan, Chris Tucker, Tom Wilkinson, Chris Penn, Elizabeth Peña.
MPAA rating: PG-13.
DVD, Dolby digital stereo.
Closed-captioned.
Keywords: United States. -- Federal Bureau of Investigation -- Drama; Police -- California -- Los Angeles -- Drama; Kidnapping -- California -- Los Angeles -- Drama; Los Angeles (Calif.) -- Drama; Police films; Video recordings for the hearing impaired; Fiction films; Feature films; Comedy films